Kolaborasi dan Manajemen Pengetahuan dalam Pengelolaan Zakat, Infak dan Sedekah Di Kota Tanjungpinang - Geiyono, Suwa; MUHAMMAD, ADJI SURADJI; Yudiatmaja, Wayu Eko (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
The potential of zakat in the city of Tanjungpinang is indeed enough to increase every year. However, the management is considered not optimal because there is no collaboration carried out continuously with other zakat management actors. In Tanjungpinang itself there are institutions that participate in the process of managing zakat and collecting zakat. Lazismu is one of the institutions that participated in the collection and distribution process but has never collaborated with Baznas. Unlike the UPZ formed by Baznas, this unit is an extension of the collection process in the SKPD, Mosques, Schools and BUMD sectors. This study uses qualitative research methods with an explorative approach to data collection techniques namely; interviews, observation and documentation. This study aims to examine collaboration in creating knowledge through knowledge management in zakat management, infaq, and alms which focus on the process of creating innovation in the development of zakat, infaq and alms. The theory used is collaboration theory and knowledge management with two types of knowledge namely explicit and implicit. Based on the results of the study found that the analysis of the existence of innovation in the development of zakat, infaq and alms in the city of Tanjungpinang can not be said to be successful because it does not maximize the knowledge possessed by the members of the organization. In addition, the obstacles that are found are regulatory issues that have not yet been implemented. Regulatory issues are the main priority that must be addressed with the aim of getting material and moral encouragement from the local government. Keywords: Collaboration, Knowledge Management, ZIS